Rare gynecological entity: malignant cervical PEComa (perivascular epithelioid cell differentiation tumour) - challenges in diagnosis, treatment and surveillance - Anjos, Amanda da Silva; Kwiatkowski, Filipe Vieira; Kwiatkowski, Rafael Vieira; Bonow, Danielle Rediess; Vasques, Luana Ferreira; Teixeira, Sabine Triguero (Brazilian Journal of Oncology, 2024)
Perivascular epithelioid cell tumors constitute a family of mesenchymal tumors characterized by the concomitant expression of melanocytic and muscular markers. Gynecological perivascular epithelioid cell tumors are rare, encompassing about 25% of cases. Studies demonstrate an even rarer occurrence in the uterine cervix. In this article, we report a case of malignant perivascular epithelioid cell tumors of the uterine cervix in a young patient, managed with total hysterectomy with unilateral salpingo- oophorectomy (due to suspected neoplasic involvement of the right ovary) and bilateral pelvic lymphadenectomy. Due to limited data, diagnosing these tumors is challenging. Given the uncertain biological behavior of this neoplasm, they should be considered potentially malignant and require long-term follow-up, despite the potential for late local recurrence and distant metastases. Surgical treatment involving complete resection of the lesion with clear margins remains the recommended option for this type of tumor until more consistent evidence can support adjuvant treatments.
Keywords: Uterine cervical neoplasms; Perivascular epithelioid cell neoplasms; Hysterectomy